2012
DOI: 10.1155/2012/819382
|View full text |Cite
|
Sign up to set email alerts
|

Medical Gases: A Novel Strategy for Attenuating Ischemia—Reperfusion Injury in Organ Transplantation?

Abstract: Ischemia reperfusion injury (IRI) is an inevitable clinical consequence in organ transplantation. It can lead to early graft nonfunction and contribute to acute and chronic graft rejection. Advanced molecular biology has revealed the highly complex nature of this phenomenon and few definitive therapies exist. This paper reviews factors involved in the pathophysiology of IRI and potential ways to attenuate it. In recent years, inhaled nitric oxide, carbon monoxide, and hydrogen sulfide have been increasingly ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Likewise, the effect of peroxynitrite can be neutralized by H 2 S in brain endothelial cells during oxidative stress and in liver, heart and lung during I/R injury [11; 176], possibly through chemical mechanisms discussed above. Along this line, it has been suggested that a combination of NO and H 2 S therapy may be a better option for treatment of I/R injury after organ transplantation to effectively balance the impact of each molecule on ROS toxicity [177]. However, additional studies are needed to more comprehensively examine the effect of H 2 S on ROS formation and associated defense pathways, as it is likely that both are affected.…”
Section: H2s Interactions With No and Other Biochemical Moleculesmentioning
confidence: 99%
“…Likewise, the effect of peroxynitrite can be neutralized by H 2 S in brain endothelial cells during oxidative stress and in liver, heart and lung during I/R injury [11; 176], possibly through chemical mechanisms discussed above. Along this line, it has been suggested that a combination of NO and H 2 S therapy may be a better option for treatment of I/R injury after organ transplantation to effectively balance the impact of each molecule on ROS toxicity [177]. However, additional studies are needed to more comprehensively examine the effect of H 2 S on ROS formation and associated defense pathways, as it is likely that both are affected.…”
Section: H2s Interactions With No and Other Biochemical Moleculesmentioning
confidence: 99%
“…Additionally, in an animal model of cerebral ischemia, the inhalation of hydrogen gas proved to serve as a neuroprotectant through its role in reducing oxidative stress under conditions where reperfusion injury was shown to lead to apoptotic cell death [92,93]. Other gases used therapeutically across tissue models of ischemia-reperfusion include nitric oxide, hydrogen sulfide and carbon monoxide [29,94,95,96]. …”
Section: Neuroprotective Strategiesmentioning
confidence: 99%
“…Preventive therapies might include ischemic conditioning involving short, nonlethal episodes of ischemia [1], several metabolic intervention options [2,3], therapeutic gas application [4], modulation of nucleotide signaling [5,6 && ] or microRNA application [7]. Targeting innate and adaptive immune activation by inhibiting Toll-like receptor (TLR) signaling [8], complement activation [9] or inducing the recruitment of regulatory T cells [10] might promote the therapeutic effects against IRI.…”
Section: Introductionmentioning
confidence: 99%